Evaluasi Penerapan Kebijakan Pengelolaan Arsip Dinamis Dengan Model CIPP (Context, Input, Process, Product) pada Procurement Unit PT Asuransi Jasa Indonesia - Fani Erisha Dewi; Roni Faslah; Ria Rahma Nida (Indo Publishing, 2026)
This study aims to evaluate the implementation of the Archival Governance Policy in managing dynamic records at the Procurement Unit of PT Asuransi Jasa Indonesia using the CIPP (Context, Input, Process, Product) evaluation model. The background of this research is based on the importance of systematic dynamic records management in supporting accountability, transparency, and audit readiness in procurement activities characterized by high document intensity. This study employed a descriptive qualitative approach. Data were collected through indepth interviews, observation, and documentation studies involving employees directly engaged in procurement records management. The findings indicate that, in terms of context, the policy is normatively aligned with the unit’s operational needs, and in the product aspect, it has contributed positively to improving document organization, quality, and audit preparedness. However, within the input and process dimensions, several challenges remain, including disparities in employee understanding, limited physical archival space, suboptimal utilization of the Document Management System (DMS), and the absence of structured and continuous monitoring mechanisms. The study concludes that the effectiveness of policy implementation is not solely determined by the existence of formal regulations, but also by human resource readiness, infrastructure support, procedural consistency, and systematic evaluation mechanisms.